2024
DOI: 10.3847/1538-4365/ad1c67
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Broad Emission Line and Doppler Factor Estimation for Fermi Blazars

Guohai Chen,
Zepeng Zheng,
Xiangtao Zeng
et al.

Abstract: In this work, we obtained a sample of 979 Fermi blazars with broad emission lines, including 701 objects collected from published works and 278 objects developed in this work. For the 278 objects, we made a crossmatch from three catalogs, the Fermi Large Area Telescope Fourth Source Catalog (4FGL), the Sloan Digital Sky Survey, and the Large Sky Area Multi-Object Fiber Spectroscopic Telescope, and calculated the broad-line region (BLR) luminosity. Then, we estimated the Doppler factor and studied the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Following works based on various multiband data just confirmed that the emissions in blazars is strongly beamed and affects the observational phenomenon known as "blazar sequence" (e.g., Fan et al 2017;Ouyang et al 2023;Wan et al 2024). In our study we did not apply the Doppler factor as one of the parameters because it is estimated for a limited number of blazars, e.g., for 979 Fermi blazars in one of the recent studies (Chen et al 2024). Therefore, we cannot test the intrinsic nature of the blazar sequence.…”
Section: Discussionmentioning
confidence: 89%
“…Following works based on various multiband data just confirmed that the emissions in blazars is strongly beamed and affects the observational phenomenon known as "blazar sequence" (e.g., Fan et al 2017;Ouyang et al 2023;Wan et al 2024). In our study we did not apply the Doppler factor as one of the parameters because it is estimated for a limited number of blazars, e.g., for 979 Fermi blazars in one of the recent studies (Chen et al 2024). Therefore, we cannot test the intrinsic nature of the blazar sequence.…”
Section: Discussionmentioning
confidence: 89%
“…Second, a collection from Zhang et al (2020Zhang et al ( , 2022 and their respective references (briefly denoted as Z22), was employed. Lastly, new extensions from our preliminary work cited from Chen et al (2024) (marked as C24) were added. These expanded FSRQs collected from C24 had their full width at half maximum (FWHM) and continuum luminosities related to emission lines derived with the available software PyQSOFit (Guo et al 2018).…”
Section: Emission From the Blrmentioning
confidence: 99%
“…) ); column (10): the references for black hole mass. The references in columns (6) and (10) correspond to the literature such as Zhang et al (2020Zhang et al ( , 2022, Paliya et al (2021), andChen et al (2024). The symbol "TW" signifies that we calculate the black hole mass in this study.…”
Section: Emission From the Blrmentioning
confidence: 99%
See 1 more Smart Citation